Enhanced direct sequence spread spectrum (eDSSS) Method to Mitigate SINR mismatch in LTE-Wi-Fi integrated networks - Azita Laily Yusof; Ainnur Eiza Azhar; Norsuzila Ya'acob (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Demand of data usage and increase of subscribers in Long Term Evolution (LTE) has urged Third Group Partnership Project (3GPP) to find a solution of traffic data growth. In Release 12, the 3GPP introduced Wi-Fi as an alternative to ease the heavy traffic at the LTE base station in dense areas. In contrary with the traffic offloading, Wi-Fi users suffer the worst network degradation because of co-channel interference at frequency 2.4GHz due to collided with LTE band 40. Interference management in LTE-Wi-Fi integrated network is crucial as it affect user’s experiences and services. In this paper, we enhanced a method which is Direct Sequence Spread Spectrum (DSSS) to improve user’s performance in LTE-Wi-Fi network. The DSSS has advantages such as more robust and ability to expand to higher data rates. We introduce a new coefficient called as chip rate coefficient (α) to investigate Signal-to-Interference-Noise Ratio (SINR) expression for User Equipments (UEs) in LTE-Wi-Fi networks. The simulation results discovered that proposed α with value of 0.2 gave the optimum improvement of SINR for LTE and Wi-Fi users. By modifying the SINR expression of the standard DSSS, SINR values at MUE and WUE show better improvement with 4.69% and 17.94%, respectively.